2011
DOI: 10.1371/journal.pone.0016946
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Predictors of Immune Reconstitution Inflammatory Syndrome in a Rural Area of Mozambique

Abstract: BackgroundThere is limited data on the epidemiology of Immune Reconstitution Inflammatory Syndrome (IRIS) in rural sub-Saharan Africa. A prospective observational cohort study was conducted to assess the incidence, clinical characteristics, outcome and predictors of IRIS in rural Mozambique.MethodsOne hundred and thirty-six consecutive antiretroviral treatment (ART)-naïve HIV-1-infected patients initiating ART at the Manhiça district hospital were prospectively followed for development of IRIS over 16 months. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 34 publications
(56 reference statements)
3
33
0
1
Order By: Relevance
“…Retrospective studies from Mexico (22) and Mozambique (23) of 390 and 136 patients respectively initiating ART indicate that the incidence of IRIS is approximately 27%. The vast majority of IRIS cases are associated with opportunistic infections (OI) either recognized prior to initiation of ART but worsening after therapy (paradoxical IRIS) or recognized after therapy initiation due to the restoration of the immune system (unmasking IRIS) (Figure 1).…”
Section: Incidence Of Iris and Cns-irismentioning
confidence: 99%
“…Retrospective studies from Mexico (22) and Mozambique (23) of 390 and 136 patients respectively initiating ART indicate that the incidence of IRIS is approximately 27%. The vast majority of IRIS cases are associated with opportunistic infections (OI) either recognized prior to initiation of ART but worsening after therapy (paradoxical IRIS) or recognized after therapy initiation due to the restoration of the immune system (unmasking IRIS) (Figure 1).…”
Section: Incidence Of Iris and Cns-irismentioning
confidence: 99%
“…14 Severely immunocompromised patients who are ART-naive at OI diagnosis 1 and those with low CD4 counts appear to be most susceptible to IRIS. 2,15,16 Other risk factors include high HIV-1 RNA levels before ART, 2 a more rapid initial HIV-1 RNA suppression, 1,17 a high OI-derived antigen load at the time of ART initiation, 3,18 a short time interval between diagnosis and/or treatment start of an OI and ART initiation, 1,3,16 and a low body mass index. 15 Nonetheless, reports are not consistent, and it has been suggested that risk factors might differ by mode of IRIS presentation and etiology.…”
Section: Introductionmentioning
confidence: 99%
“…2,15,16 Other risk factors include high HIV-1 RNA levels before ART, 2 a more rapid initial HIV-1 RNA suppression, 1,17 a high OI-derived antigen load at the time of ART initiation, 3,18 a short time interval between diagnosis and/or treatment start of an OI and ART initiation, 1,3,16 and a low body mass index. 15 Nonetheless, reports are not consistent, and it has been suggested that risk factors might differ by mode of IRIS presentation and etiology. 13,15 Most studies to date trying to elucidate potentially diagnostic risk factors and/or biomarkers of IRIS have focused on patient groups with a particular opportunistic infection, such as Mycobacterium tuberculosis (TB), 16,[19][20][21] Mycobacterium avium, and intracellulare complex (MAC), 22 Cryptococcus neoformans, 3,14,18 or CMV.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the complications that an individual can experience on HAART is immune reconstitution inflammatory syndrome (IRIS) (Letang, Miro et al 2011). IRIS is seen in individuals recovering from immunodeficiency.…”
Section: Highly Active Antiviral Therapy (Haart)mentioning
confidence: 99%